Digital first personality: Automation and influence within evolving media ecologies. (December 2020) - Hutchinson, Jonathon
This article is about the new roles within social media as a result of the software that automatically gathers and influences our usage: digital first personalities. I use cultural intermediation as a framework to locate the automated processes, such as algorithmic generated recommender systems, that influence content consumption practices driven by digital first personalities. First, the article applies cultural intermediation to celebrity, social media influencers and algorithms to highlight how media is produced and distributed by new forms of intermediation. This section outlines the new players in social media, how the value of media content is transferred from one stakeholder group to another and how algorithms increasingly place prominence on particular types of content. The article then presents fieldwork from several digital agencies that are responsible for creating the digital first personality role. These agencies are demonstrable of those that produce commercially oriented content alongside other more public affairs-oriented content. Finally, the article argues that digital first personalities are crucial actors within cultural intermediation to ensure public issues remain visible to those stakeholders who are most impacted by timely information on societal issues.